2019
DOI: 10.3389/fpls.2019.01002
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly of the Pokeweed Genome Provides Insight Into Pokeweed Antiviral Protein (PAP) Gene Expression

Abstract: Ribosome-inactivating proteins (RIPs) are RNA glycosidases thought to function in defense against pathogens. These enzymes remove purine bases from RNAs, including rRNA; the latter activity decreases protein synthesis in vitro , which is hypothesized to limit pathogen proliferation by causing host cell death. Pokeweed antiviral protein (PAP) is a RIP synthesized by the American pokeweed plant ( Phytolacca americana ). PAP inhibits virus infection when expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 168 publications
1
5
0
Order By: Relevance
“…The Bougainvillea RIPs possess transcriptional polymorphism, and all the isoforms exhibit diversified expression in the different seasons. It was previously shown that the expression of each isoform is affected by a cis-acting element that combines with the transcription factor under jasmonic acid stress [ 17 ]. Besides this, the Bougainvillea RIPs have a close genetic relationship with PAP, which alters the splicing of viral RNA and reduces viral infection [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bougainvillea RIPs possess transcriptional polymorphism, and all the isoforms exhibit diversified expression in the different seasons. It was previously shown that the expression of each isoform is affected by a cis-acting element that combines with the transcription factor under jasmonic acid stress [ 17 ]. Besides this, the Bougainvillea RIPs have a close genetic relationship with PAP, which alters the splicing of viral RNA and reduces viral infection [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms are differentially expressed during leaf development, wounding, and abscisic acid treatment, which suggests that RIP isoforms may play diversified roles during stress responses [ 16 ]. Some studies have shown that plants express various RIP isoforms to improve their defense systems to cope with the stress caused by environmental changes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, experimental evidence has confirmed the control of the expression of RIPs at the gene level during abiotic and biotic stress in plants [39,40]. The de novo assembly of the pokeweed (P. americana) genome showed that the genes of both the pokeweed antiviral protein (PAP) and the PAP isoforms exhibited a long 5 UTR containing one intron and cis-regulatory elements associated with diverse biotic and abiotic stresses [41].…”
Section: Gene Organization Of Quinoinmentioning
confidence: 97%
“…This model was similar to the gene models retrieved for the PAP isoforms. Therefore, the gene organization suggested that quinoin protein expression could be subjected to particular gene regulation in biotic and abiotic stresses given the presence of the 5 UTR region of both the intron and the leader intron [41].…”
Section: Gene Organization Of Quinoinmentioning
confidence: 99%
“…However, these data were both achieved by second generation sequencing (SGS), which could not produce full-length transcripts. Genomic data of P. americana was available at the SRA under project PRJNA544344, but it's raw reads without coding sequences prediction and functional annotation [7].…”
Section: Introductionmentioning
confidence: 99%